Visualizing Distance, Erasing Voice: A Multimodal Discourse Analysis of @rfi’s Sumatra Flood Disaster Coverage - Farah Risma Eka Putriana; Marliza Arsiyana (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2026)
This study examines how the affected community of the 2025 Sumatra flood disaster is visually and discursively represented in an eight-photograph Instagram carousel published by the international news outlet Radio France Internationale (@rfi). Guided by Kress and van Leeuwen's (2006) Multimodal Discourse Analysis and its tripartite model of representational, interactive and compositional metafunctions, this study undertakes a qualitative close reading of both the visual and verbal layers of the carousel to determine the extent to which the local community is included as a legitimate, voiced participant in the narrative of its own disaster, as opposed to being reduced to a passive recipient of institutional rescue or an anonymous statistic of loss. The analysis finds that visual inclusion in the carousel is graded and frequently contradictory rather than binary: institutional actors such as search-and-rescue personnel and military aircraft are consistently constructed as agents endowed with narrative, interactive and compositional dominance, while the affected community oscillates between brief moments of agency, symbolic abstraction and complete representational absence. The single instance in which a community member directly addresses the viewer through gaze is immediately undercut by a compositional text overlay reporting the death toll across her body, while the two photographs depicting the clearest community agency receive no acknowledgment whatsoever in the accompanying caption. This study identifies these patterns as a false individualization arc and a multimodal disjunction between visual presence and discursive voice, demonstrating that a community can be made visible within a disaster narrative while remaining systematically unheard. As a single-case analysis of one carousel from one outlet, this study does not permit generalization across platforms, disaster events or news organizations and its findings should be read as an in-depth diagnostic instance rather than a representative sample of Global North disaster coverage. Nonetheless, by extending Kress and van Leeuwen's (2006) framework beyond static print and single-image analysis to the sequential, multi-image logic of social media carousels, this study offers a replicable analytical model for detecting the gap between visibility and voice and contributes a concrete methodological entry point for future comparative research into how Global South communities are positioned within Global North disaster journalism.